A BIBLIOMETRIC ANALYSIS OF THE EUROPEAN RESEARCH IN HYPERTENSION. (June 2018) - Menard, J.; Devos, P.
Abstract : Objective: By using bibliometric indicators, we have analyzed the scientific production of European countries in the field of hypertension. Design and method: Articles were extracted from the PubMed database using a query based on Mesh Terms, titles and journals. Publications were then analyzed in Web of Science and InCites (©Clarivate Analytics) in order to extract citations and addresses. Two indicators were analyzed: total number of articles, and percentage of articles in the Top 1% (articles among the 1% of the most cited articles worldwide). Guidelines and general reviews were excluded after reading all abstracts. Results: The worldwide number of research papers in Pubmed increases from nearly 400 000 articles in 1996 to nearly 1 000 000 in 2015. For hypertension, it increases from 4000 to 6500. During the period 2006–2015, the worldwide research production in hypertension increased from 4644 to 6451 articles (+ 39%). From 2006 to 2015, contribution of the Asian region increased from 22.8 % to 36.3 % (3.9% to 16.0% for China), that of the USA decreased from 31.9 % to 30.2 %, and that of the 25-European Union countries from 40.4 % to 33.4 %. In Europe, contribution of United Kingdom was 7.0 % of the total number of articles, followed by Italy (6.5%), Germany (6.4%), France (4.1%), Netherlands (3.7%), Spain (3.4%) ... During 2006–2015, 436 articles among 55, 868 were in the top 1% most cited (0.78% instead of the expected 1%), respectively 0.57% for the Asian region (0.54% for China), 1.42% for USA, and 1.18% for EU25. Percentages of participation in the European Top 1% articles were respectively 39.8% for United Kingdom, 25.1% for Germany, 19.3% for Italy, 15.2% for The Netherlands and 13.5% for France, 12.3% for Spain. The European Top 1% included 53 randomized controlled trials, 16 meta analysis, and 40 clinical, 34 epidemiological, 19 experimental and 9 genetic studies. Conclusions: Bibliometric analysis, if performed with a 5 to 10 years periodicity, could help each country to take strategical decisions about their own research in hypertension and look for optimal cooperation with other countries.